Implementation of International Relations on Illegal Fishing Activities by Chinese Fisherman in the Exclusive Economic Zone of the Republic of Indonesia Natural Island - Michelle Angelika S; Yohanes Firmansyah; Hanna Wijaya; Yana Sylvana (International Journal of Social Science and Religion (IJSSR), 2020)
The territorial sea is the area of the sea zone closest to the coast, entirely subject to coastal sovereignty. Meanwhile, what is meant by the Economic Exclusive Zone is an area outside and adjacent to the territorial sea whose boundaries are 200 nautical miles measured from the base of the coast. The northern Natuna Islands are an Indonesian territorial area included in the Economic Exclusive Zone of the Republic of Indonesia. In areas that are the source of the power of nature are plentiful, including a source of power sea. It's led to interest from the foreigners to master the source power. The state of China announced that territory northwest china south is the territory of china based Map nine-dash line, which triggers the occurrence of the disputed territory of sea between Indonesia and china because it crosses the boundary north is Natuna Island the impact on the ships of foreign without permission to enter and steal the source power of nature in the Economic Exclusive Zone of the Republic of Indonesia because it is the actual effort of government Indonesia to eradicate illegal fishing both through relationship diplomacy maritime and businesses more. Researchers using qualitative descriptive research. The methodology of qualitative as the procedure of research that produces the descriptive data form of words written or spoken of people and behaviors that can be observed.